English Studies from Global to Nepali Context: Critical Debates, Challenges and Possibilities - Khadka, Thir Bahadur (Journal of NELTA Koshi (JoNK), 2024)
This paper aims to present an analysis of the critical debates in the area of English Studies emerged from the time of its initiation and still going on, various challenges that this discipline has undergone, and its future prospects. Based on library research method, the analysis of the relevant online and physical library materials related to English Studies has been conducted. The findings show how English Studies has undergone the critical debates like whether English is the subject of colonial domination or socially progressive project, whether it has to give privileges to literary studies or creative writing, and whether it has to adopt a single standarised form of English or world Englishes. In addition to it, it shows that despite undergoing a number of critical debates and challenges due to either the ongoing process of departmentalisation or the African abolitionist movements, English Studies has become refined, updated and interdisciplinary area of study. Proper redesign and reformulation of English courses, incorporation of local art, culture and literature, adoption of new technology and vocational aspects etcetera could make it more relevant, effective and impactful in the days to come.